Tax holiday: Akselerasi Indonesia menuju green mobility dan natural sustainability - Susilawati Susilawati; Indah Masri; Lazarus Sinaga; Friska Lasmaria Wulandari Siahaan (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2025)
This study presents a comprehensive systematic literature review to integrate the literature on the effect of tax holidays on renewable energy investments, namely the electric vehicle industry (Green Mobility) and natural sustainability. By analyzing 10 final articles from the Scopus, Web of Science, and Google Scholar databases published between 2020 and 2025, this study aims to analyze tax holiday policies in the context of green mobility and natural sustainability, assess their impact on green investment, identify obstacles or challenges and recommendations for sustainable fiscal policies based on data in accelerating the adoption and development of electric vehicles in Indonesia as part of the national green economy agenda. The results of this study show that tax holidays affect green investments in the electric vehicle industry (Green Mobility) and natural sustainability, as well as fiscal strategies to address the challenges of the electric vehicle industry towards a natural, sustainable Indonesia.